Adaptive Koopman-Based Models for Holistic Controller and Observer Design - Junker, Annika; Pape, Keno Egon Friedrich; Timmermann, Julia; Trächtler, Ansgar (IFAC-PapersOnLine)
Keywords: General Medicine

Tool Wear Monitoring of a Tree Log Bandsaw using a Deep Convolutional Neural Network on challenging data - Koppert, Steven; Henke, Christian; Trächtler, Ansgar; Möhringer, Stefan (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Learning Data-Driven PCHD Models for Control Engineering Applications* - Junker, Annika; Timmermann, Julia; Trächtler, Ansgar (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Output tracking for a non-minimum phase robotic manipulator - Berger, Thomas; Lanza, Lukas Johannes (IFAC-PapersOnLine)
We exploit a recently developed funnel control methodology for linear non-minimum phase systems to design an output error feedback controller for a nonlinear robotic manipulator, which is not minimum phase. We illustrate the novel control design by a numerical case study where we simulate end-effector output tracking of the robotic manipulator.

Exact solution to a special class of nonlinear MPC problems - Schulze Darup, Moritz; Klädtke, Manuel; Mönnigmann, Martin (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Teaching MPC: Which Way to the Promised Land? - Faulwasser, Timm; Lucia, Sergio; Schulze Darup, Moritz; Mönnigmann, Martin (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Encrypted MPC based on ADMM real-time iterations - Darup, Moritz Schulze (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Bifurcation preserving discretisations of optimal control problems - Offen, Christian; Ober-Blöbaum, Sina
The first order optimality conditions of optimal control problems (OCPs) can be regarded as boundary value problems for Hamiltonian systems. Variational or symplectic discretisation methods are classically known for their excellent long term behaviour. As boundary value problems are posed on intervals of fixed, moderate length, it is not immediately clear whether methods can profit from structure preservation in this context. When parameters are present, solutions can undergo bifurcations, for instance, two solutions can merge and annihilate one another as parameters are varied. We will show that generic bifurcations of an OCP are preserved under discretisation when the OCP is either directly discretised to a discrete OCP (direct method) or translated into a Hamiltonian boundary value problem using first order necessary conditions of optimality which is then solved using a symplectic integrator (indirect method). Moreover, certain bifurcations break when a non-symplectic scheme is used. The general phenomenon is illustrated on the example of a cut locus of an ellipsoid.
Keywords: optimal control; catastrophe theory; bifurcations; variational methods; symplectic integrators

Encrypted cloud-based MPC for linear systems with input constraints - Schulze Darup, Moritz; Redder, Adrian; Quevedo, Daniel E. (IFAC-PapersOnLine)

A Multiobjective MPC Approach for Autonomously Driven Electric Vehicles * *This research was funded by the German Federal Ministry of Education and Research (BMBF) within the Leading-Edge Cluster Intelligent Technical Systems OstWestfalenLippe (it’s OWL). - Peitz, Sebastian; Schäfer, Kai; Ober-Blöbaum, Sina; Eckstein, Julian; Köhler, Ulrich; Dellnitz, Michael (IFAC-PapersOnLine)

A multiobjective MPC approach for autonomously driven electric vehicles - Peitz, Sebastian; Schäfer, Kai; Ober-Blöbaum, Sina; Eckstein, Julian; Köhler, Ulrich; Dellnitz, Michael (Proceedings of the 20th World Congress of the International Federation of Automatic Control (IFAC))
We present a new algorithm for model predictive control of non-linear systems with respect to multiple, conflicting objectives. The idea is to provide a possibility to change the objective in real-time, e.g. as a reaction to changes in the environment or the system state itself. The algorithm utilises elements from various well-established concepts, namely multiobjective optimal control, economic as well as explicit model predictive control and motion planning with motion primitives. In order to realise real-time applicability, we split the computation into an online and an offline phase and we utilise symmetries in the open-loop optimal control problem to reduce the number of multiobjective optimal control problems that need to be solved in the offline phase. The results are illustrated using the example of an electric vehicle where the longitudinal dynamics are controlled with respect to the concurrent objectives arrival time and energy consumption.

Inverse Optimal Control Problem: the Sub-Riemannian Case - Jean, Frédéric; Maslovskaya, Sofya; Zelenko, Igor (IFAC-PapersOnLine)